Faculty perceptions regarding community-based medical education: The case of KSA - Mahrous, Mohamed S. (J Taibah Univ Med Sci, 2017)
OBJECTIVES: There is great concern about the selection and quality of health college graduates and about their ability to respond to local community health needs. Community-based medical education (CBME) is a means of achieving educational relevance to community needs. In KSA, medical education has rapidly progressed in tandem with huge expansions in community health needs and expectations. This study aimed to assess the perceptions of the faculty members of the colleges of medicine and dentistry towards different concepts reflecting CBME. METHODOLOGY: This analytical, observational and cross-sectional study used a self-administered questionnaire that was given to the faculty members of the colleges of medicine and dentistry at Taibah University, KSA. RESULTS: As many as 136 faculty members responded, a response rate of 64%. The percentage of agreement was strongest among the faculty members of the college of medicine. The study findings also showed a relationship between different concepts of CBME and faculty teaching experiences by academic positions for applying CBME. There were significant differences in the social, cultural, and ethnic aspects of medical practice. CONCLUSION: CBME is a means of achieving educational relevance to community needs and consequently serves as a means of implementing a community-oriented education programme.